Identification of Bacterial Leaf Blight Resistance (Xanthomonas oryzae pv. oryzae) Genes in Advance Breeding Lines of Rice (Oryza sativa L.) through Molecular Markers - Nirala, Devarchan; Sahu, Naresh Kumar; Singh, Bharti; Kumar, Vikky; Surekha; Sahu, Hemant; Sao, Abhinav; Nair, Sunil (International Journal of Bio-resource and Stress Management, 2025)
The present study was conducted kharif (July–October, 2023) at Department of Genetics and Plant Breeding, IGKV, Raipur, Chhatisgarh, India to determine the presence of three Bacterial leaf Blight genes (xa5, xa13 and Xa21) in rice by utilizing the gene specific markers in the advance breeding lines. This experiment utilized 37 advance breeding lines from a cross having suitable donor parent (for resistant BLB genes), and the developed lines were further utilized to determine the presence of resistance genes. MAS for three BLB genes was done using gene specific markers namely viz., pTA248, xa13 prom, xa13, xa5R, Xa21, RM13, RM31 and RM122. Among these eight gene specific markers three markers pTA248 for the Xa21 gene, xa13 prom for the xa13 gene and xa5R marker for the xa5 gene, were shown to be polymorphic across donor and recurrent parents. These three markers were utilized to detect the presence of resistance genes in the population. The results revealed that eight plants have been present all the three genes while rest plants have been found two or single gene. 13 plants were found positive for two gene combination (Xa21+xa13) while 12 plants were found for gene combination (Xa21+xa5) and 10 plants were found gene combination of (xa13+xa5). These two gene combination and 3 gene combination plants will be further utilize as breeding materials for development of BLB resistant cultivars.